Phytochemical mediated modulation of COX-3 and NFκB for the management and treatment of arthritis - Dipak Biswas; Bharat Gopalrao Somkuwar; Jagat Chandra Borah; Pritish Kumar Varadwaj; Saurabh Gupta; Zeeshan Ahmad Khan; Gopinath Mondal; Asamanja Chattoraj; Lokesh Deb (Scientific Reports, 2023)
Abstract In this study, we investigated whether zerumbone (ZBN), ellagic acid (ELA) and quercetin (QCT), the plant-derived components, can modulate the role of COX-3 or cytokines liable in arthritic disorder. Initially, the effect of ZBN, ELA, and QCT on inflammatory process was investigated using in-vitro models. In-silico docking and molecular dynamics study of these molecules with respective targets also corroborate with in-vitro studies. Further, the in-vivo anti-arthritic potential of these molecules in Complete Freund’s adjuvant (CFA)-induced arthritic rats was confirmed. CFA increases in TNF-α and IL-1β levels in the arthritic control animals were significantly (***p < 0.001) attenuated in the ZBN- and ELA-treated animals. CFA-induced attenuation in IL-10 levels recovered under treatment. Moreover, ELA attenuated CFA-induced upregulation of COX-3 and ZBN downregulated CFA-triggered NFκB expression in arthritic animals. The bonding patterns of zerumbone in the catalytic sites of targets provide a useful hint in designing and developing suitable derivatives that can be used as a potential drug. To our best knowledge, the first time we are reporting the role of COX-3 in the treatment of arthritic disorders which could provide a novel therapeutic approach for the treatment of inflammatory disorders.